TEKNIK MODELLING MENGGUNAKAN TELEVISI SEBAGAI MEDIA PEMBELAJARAN DALAM PENANAMAN KARAKTER SISWA - Hanipah, Sri; Sa'adah, Sa'adah; Sulistyawati, Anita (LPPM STKIP PGRI Bandar Lampung, 2020)
The COVID-19 pandemic requires that studying at home requires students to study independently which has an impact on student character. This study aims to determine the use of television as a medium of learning in inculcating the character of students who are independent, curious, and responsible. This type of research is qualitative research. The population of this research is the fifth-grade students of SD 026 Teluk Kabung, Gaung District, Indragiri Hilir Regency, Riau Province. The results of the study show that modelling techniques using television as a learning medium can foster students' independent character, curiosity, and responsibility. The benefits of this research can add to the repertoire in the field of character education.